New successes with organic pesticides 1 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
New successes with organic pesticides Jatropha curcas, an euphorbiaceous shrub familiar to West African villagers, has been shown to be a very effective pesticide. Jatropha is often planted as a hedge to protect crops: its leaves and fruit are...